Evaluation influence: Method and societal phenomenon. (July 2019) - Høydal, Øyunn Syrstad
Questions concerning influence are essential in the field of evaluation. This article argues for a dual perspective in this discussion. Theories of influence are combined with the idea of The Evaluation Society, and together these create a broad perspective on the use of evaluations and their possible impact. From this dual perspective, evaluation is recognized both as a method for planning and development and as an independent societal phenomenon. Norwegian participation in the Programme for International Student Assessment (PISA) is used to illustrate the essence of this dual perspective and how it can yield a more complete understanding of the complexity of evaluation impact.